1983
DOI: 10.1017/s0031182000082895
|View full text |Cite
|
Sign up to set email alerts
|

A dosing technique and the effects of sub-lethal doses of Nosema fumiferanae (Microsporida) on its host the spruce budworm, Choristoneura fumiferana

Abstract: SummaryVarious dosages of the microsporidian parasite, Nosema fumiferanae were fed to 12-day-old larvae of Choristoneura fumiferana using a previously undescribed bioassay capsule. A spore dose of 3 × 104 resulted in 92% infection and a significant reduction in pupal weights, adult female longevity and a mean spore concentration of 1·5 × 107/living adult. Significant mortality (68%, combined larvae and pupae) did not occur until larvae ingested 3 × 107 spores; this dose produced a mean of 1·8 × 107 spores in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…L OTMAR (1940) needed 1 000 spores/bee to produce N. apis infections in 28 % of the tested animals. Estimates for N. algerae infecting Anopheles albimanus (A VERY & A NTHONY , 1983) and N. fumiferanae infecting Choristoneura fumiferana (W ILSON , 1983) (1984) claims that the infection is spread from the anterior to the posterior ventricular parts. In contrast, K ELLNER (1980) found the growing infection to spread from the posterior to the anterior parts of the ventriculus.…”
Section: Introductionmentioning
confidence: 99%
“…L OTMAR (1940) needed 1 000 spores/bee to produce N. apis infections in 28 % of the tested animals. Estimates for N. algerae infecting Anopheles albimanus (A VERY & A NTHONY , 1983) and N. fumiferanae infecting Choristoneura fumiferana (W ILSON , 1983) (1984) claims that the infection is spread from the anterior to the posterior ventricular parts. In contrast, K ELLNER (1980) found the growing infection to spread from the posterior to the anterior parts of the ventriculus.…”
Section: Introductionmentioning
confidence: 99%
“…We expect the association of these two species to be common because both Apanteles and Nosema are frequently found in natural populations of larval spruce budworm. It has also been suggested that sublethal infections by Nosema, often chronic in laboratory colonies of spruce budworm (Wilson 1980), could affect the mass rearing of budworm parasitoids (Rappaport and Page 1985).…”
Section: Introductionmentioning
confidence: 99%
“…It produces characteristic spores in the epidermal cells of its host and can be transmitted congenitally, perorally, or by injection (Thomson 1958a;Wilson 1982). Its effect on the host depends upon the intensity of infection: low to moderate doses retard growth and development of immature stages and reduce fecundity in the adult (Thomson 1958b;Wilson 1983), while higher levels of infection (more than 20 x lo6 spores/mg dry weight of host) cause death (Wilson 1985). Nosema is present in most natural spruce budworm populations but the relative frequency of infection appears to increase as high densities of spruce budworm persist in an area (Wilson 1977).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are among the most widespread pathogens of insects, causing disease in both beneficial and pest species (Sprague and Becnel, 1999), and have the potential to act as natural regulators of pest insect populations (Onstad and Carruthers, 1990;Tanada and Kaya, 1993). Microsporidia typically produce chronic infections in host populations, causing suppressed pupal weight and significant reductions in size, fecundity and adult longevity (Thomson, 1958;Wilson, 1983;Fries et al, 1984;Bauer and Nordin, 1988;Anderson and Giacon, 1992). Microsporidia may be transmitted vertically, horizontally, or by both means, depending on species-specific microsporidium-host interactions (Becnel and Andreadis, 1999;Goertz et al, 2007).…”
Section: Introductionmentioning
confidence: 99%